Upaya Pencegahan Kanker Payudara Melalui Promosi Kesehatan Reproduksi Tentang Skrining Pemeriksaan Payudara Sendiri (SADARI) Pada Wanita Usia Subur (WUS) - Wahyu Nuraisya; Nunik Ike Yuniasari (STIKES dan AKZI Karya Husada Kediri, 2022)
Breast cancer is the number one type of cancer that cause of death a woman in developed and developing countries, including Indonesia. Delay in treatment in women with breast cancer is low knowledge and has a history of breast cancer. The purpose of this activity is to provide reproductive health promotion in the hope women of reproductive age health behaviors for the better. The target of the service activity was women of reproductive age as many as 32 people in Darungan Village, Pare District, Kediri Regency. The activity method was carried out in the form of counseling (lectures) in which there were pre-tests and post-tests, video screenings and question and answer. The results achieved in this activity were that women of reproductive age experienced an increase in knowledge about Breast Self-Examination Screening from the good pre-test category by 34.4% increased to 81.25% in the post test. Breast cancer screening through reproductive health promotion by conducting a breast self-examination. Health promotion not only changes people's behavior but also changes the environment that facilitates such behavior change.